Plasmonic coupled-cavity system for enhancement of surface plasmon localization in plasmonic detectors - Ooi, Kelvin J. A. (2013)
A plasmonic coupled-cavity system, which consists of a quarter-wave coupler cavity, a resonant Fabry–Pérot detector nanocavity, and an off-resonant reflector cavity, is used to enhance the localization of surface plasmons in a plasmonic detector. The coupler cavity is designed based on transmission line theory and wavelength scaling rules in the optical regime, while the reflector cavity is derived from off-resonant resonator structures to attenuate transmission of plasmonic waves. We observed strong coupling of the cavities in simulation results, with an 86% improvement of surface plasmon localization achieved. The plasmonic coupled-cavity system may find useful applications in areas of nanoscale photodetectors, sensors, and an assortment of plasmonic-circuit devices.